Acute dietary nitrate supplementation improves cycling time trial performance - Lansley, K. E.; Winyard, P. G.; Bailey, S. J.; Vanhatalo, A.; Wilkerson, D. P.; Blackwell, J. R.; Gilchrist, M.; Benjamin, N.; Jones, A. M. (Medicine & Science in Sports & Exercise, 2011)
Purpose: Dietary nitrate supplementation has been shown to reduce the O2 cost of submaximal exercise and to improve high-intensity exercise tolerance. However, it is presently unknown whether it may enhance performance during simulated competition. The present study investigated the effects of acute dietary nitrate supplementation on power output (PO), VO2, and performance during 4- and 16.1-km cycling time trials (TT).